Modern pre-Olympic athletic training process planning system - Kazikov, I. B. (Theory and Practice of Physical Culture, 2018)
Conclusion 1. The existing national pre-Olympics training system was designed back in 1970ies and since then proved highly efficient and still relevant in the modern social, political and economic conditions. 2. The pre-Olympics training process is planned from top to bottom - first by the Ministry of Sports of the Russian Federation that develops the Pre-Olympics Training Concept and downstream by each of the Russian sport federations that work out, based on the Concept, their sports-specific Target Integrated Programs (TIP) of the pre-Olympic trainings compulsory for the lower-level training process planning entities down to the coaches that develop the individual training plans for the competitors. 3. The Target Integrated Programs are changed and amended on a yearly basis to factor in the competitive progress of the candidates for the national team in the seasonal top-ranking events. The changes and amendments are made by the Expert Council of the Ministry of Sports and the General Coaches` Councils under the relevant Russian sport federations. 4. The Russian Olympic Committee offers its own Pre-Olympics Training Program that provides the efficient and effective progress support tools for the Russian athletes competing in the top-ranking sport events under the auspices of the International Olympic Committee.